Chickpea attenuates postprandial blood glucose responses: a systematic review and meta-analysis - Eunice Mah; Cassi N. Uffelman; Traci M. Blonquist; Ding Ding Wang; Colin D. Rehm; Shellen R. Goltz; YiFang Chu (Nutrition Journal)
Abstract Background Chickpeas are a legume that may help improve glycemic control, but their acute effects on postprandial glucose and insulin responses are unclear. This systematic review and meta-analysis aimed to assess the impact of acute chickpea consumption on these outcomes in controlled, crossover trials. Methods We screened PubMed, Cochrane Central Register of Controlled Trials (CENTRAL), and Embase from inception through March 21, 2024 for acute, controlled, experimental (randomized or non-randomized) trials comparing chickpea consumption with carbohydrate-matched controls that reported on postprandial glucose and insulin responses (iAUC and Cmax). Two reviewers extracted the data and assessed risk-of-bias (RoB 2) and certainty-of-evidence (GRADE). Data were analyzed using generic inverse-variance with random-effects model. Results A total of 28 eligible studies (40 comparisons) were identified. Chickpea consumption significantly reduced postprandial glucose iAUC compared to carbohydrate-matched controls (MD: -47.89, 95% CI: -64.20, -31.58, p < 0.0001). No significant effects were observed on glucose Cmax (MD: -0.23, 95% CI: -1.48, 1.02, p = 0.7207) or insulin iAUC (MD: 50.06, 95% CI: -3771.14, 3871.26, p = 0.9795). The GRADE assessment indicated very low certainty for glucose iAUC due to heterogeneity. Conclusion Meta-analysis of controlled trials suggest that acute chickpea consumption lowers postprandial glucose iAUC, albeit with low certainty of evidence. While no significant effects were observed on glucose peak or insulin response, the findings align with previous research on pulses and glycemic control. Further high-quality studies are needed to confirm these findings, as the current evidence is of low to very low certainty. Future studies should explore the long-term effects of chickpea consumption, investigate the impact of processing methods, and include metabolically unhealthy populations to enhance generalizability. Registration This review was registered on PROSPERO (CRD42022365074).